2008
DOI: 10.1016/j.abb.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxynonenal induces p53-mediated apoptosis in retinal pigment epithelial cells

Abstract: Abstract4-Hydroxynonenal (4-HNE) has been suggested to be involved in stress-induced signaling for apoptosis. In present studies, we have examined the effects of 4-HNE on the intrinsic apoptotic pathway associated with p53 in human retinal pigment epithelial (RPE and ARPE-19) cells. Our results show that 4-HNE causes induction, phosphorylation, and nuclear accumulation of p53 which is accompanied with down regulation of MDM2, activation of the pro-apoptotic p53 target genes viz. p21 and Bax, JNK, caspase3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 58 publications
(75 reference statements)
10
96
0
Order By: Relevance
“…p53, HSF1, and DAXX) require much higher HNE concentrations for their activation (32,51). Interestingly, activation of JNK, p53, and Nrf2 has also been observed in tissues of mGsta4 knock-out mice (51,72,73). Taken together with the results of the present study showing the activation of H2A.X in mGsta4 null mice, these findings strongly suggest that the in vitro effects of HNE presented here are physiologically relevant.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…p53, HSF1, and DAXX) require much higher HNE concentrations for their activation (32,51). Interestingly, activation of JNK, p53, and Nrf2 has also been observed in tissues of mGsta4 knock-out mice (51,72,73). Taken together with the results of the present study showing the activation of H2A.X in mGsta4 null mice, these findings strongly suggest that the in vitro effects of HNE presented here are physiologically relevant.…”
Section: Discussionsupporting
confidence: 78%
“…A concentration-dependent activation and phosphorylation of p53 by HNE observed in WT p53 HepG2 cells (Fig. 6, A and B) was consistent with our previous studies with other cell types (51). However, HNE induced the activation of p21 independent of p53 because our results showed that in p53 wild type HepG2 as well as in p53 null Hep3B (Fig.…”
Section: Hne Induces Phosphorylation Of Atr and Chk1supporting
confidence: 82%
See 1 more Smart Citation
“…Thus, oxidized PUFAs stimulate apoptosis of osteoblastic OB-6 cells via a PPAR␥-dependent mechanism, consistent with previous evidence for a negative impact of RGL on osteoblast survival in vitro (55) and in vivo (51). We found that the proapoptotic effect of 4-HNE is mediated by increased oxidative stress; however, other mechanisms, for example activation of p53 (56), could also be involved. NAC (12), as well as Wnt signaling (15,16) promote osteoblast survival in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…Figure 3 Intrinsic apoptotic pathway is induced by oxidative stress, p53 and mitochondrial membrane disturbances. cyt.c: cytochrome c; HNE: hydroxynonenal; and MOMP: mitochondrial outer membrane permeabilization Sharma et al 98 showed that exogenous HNE results in the phosphorylation of p53 (on Ser 15) and its nuclear translocation in retinal epithelial cells. Such activation is involved in apoptosis induction.…”
Section: Hne: a Serial Killermentioning
confidence: 99%